Exploration of the Implementation of PKL in Achieving MBKM Goals in Accounting Study Program - Devi Febrianti; Ira Megasyara; Ninik Mas’adah (Publisher Cv. Inara, 2022)
This study aims to determine whether the internship activities that have been carried out by the accounting study program at the Muhammadiyah Lamongan University can help achieve MBKM goals and bring benefits to universities, students, and internship partner agencies. This research0 was conducted on 10 partner industries0 in the accounting study program industrial0 internship program, Faculty of Economics and Business, Muhammadiyah Lamongan University in 2021 spread across the Lamongan area, and 4 students of Accounting study program who had industrial internships that year. Data collection0 techniques used in this0 study were Forum Group Discussion (FGD), observation, interviews, and documentation. Partners fully support the industrial internship program. This partner support has an impact on the achievement of MBKM goals where the PKL program or industrial internship can improve the competence0 of graduates, both soft skills0 and hard skills0 so that they0 are better prepared to meet the needs of the world of work, prepare graduates as future0 leaders of the0 nation who have superior0 and personality, namely providing sufficient experience. to students related to direct learning in the workplace and students can solve problems that exist in the industry which can be considered as a form of learning independence. The results of the study also show that the benefits of this program can also be felt by universities and internship partner agencies. However, based0 on the results of the evaluation of the accounting department, it has not been fully maximized in implementing the PKL program or industrial internship.